Influence of early regulatory problems in infants on their development at 12 months: a longitudinal study in a high-risk sample - Sidor, Anna; Fischer, Cristina; Eickhorst, Andreas; Cierpka, Manfred (Child and adolescent psychiatry and mental health, 2013)
This study examined the extent to which regulatory problems in infants at 4 and 6 months influence childhood development at 12 months. The second aim of the study was to examine the influence maternal distress has on 4-month-old children’s subsequent development as well as gender differences with regard to regulatory problems and development.
Published: 12 October 2013
Gesehen am 27.01.2022